Moisturized and non-irritating hand gel based on sappan wood (Caesalpinia sappan l.) and limau citrus peel (Citrus amblycarpa (hassk.) ochse) extracts - Dina Y. Sari; Genta W. Lestari; Habiba F.F. Pulungan; Ira Remiyati; Ratna Widyasari (AOSIS, 2023)
Background: Hand gel is a preparation used to protect hand skin from dryness. The antioxidant compounds in sappan wood and limau citrus peel can moisturize hands by preventing the oxidation of oils and fats on the surface of the (sebaceous glands). Objective: This study aims to formulate hand gel from ethanol extract of sappan wood with a combination of limau citrus peel extract that can moisturize hands and not to cause irritation. Methods: Sappan wood and limau citrus peel simplicia were macerated using 96% ethanol. The ethanolic extracts were then formulated into hand gel by varying the concentration of the ethanol extracts. The evaluation of the hand gel involved an organoleptic test, homogeneity test, pH test, spreadability test, viscosity test, and skin moisture test. A primary irritation test was carried out to ensure the hand gel's safety. Results: The results shows that the three hand gel formulas produce an orange-red color and soft scent of roses and citrus, with a pH of 7.8 and with good homogeneity. The formulas also have a spreading level of FI (5 cm), FII (5.2 cm), and FIII (5, 1 cm), and viscosity values were FI 12000 mPas, F II 12500 mPas, and F III 12400 mPas. The humidity test results on the three formulas shows different moisture values of 45.16%, 46.17%, and 45.09%, respectively (category of normal or moisture). The hand gel formulas have an irritation index of 0 (no irritation category). Conclusion: The hand gel formulas meet the quality requirements of hand gel, have moisturizing agent, and are not irritating.